Trigger warnings, covenants of presence, and more: Cultivating safe space for theological discussions about sexual trauma - Crumpton, Stephanie M. (Teaching theology and religion, 2017)
Sexual assault is prevalent, but many educators find themselves ill-prepared to address it in the classroom. This article conceptualizes a trauma sensitive pedagogy that engages the psychological, social, and theological implications of sexual assault for classroom conversations about sex and sexuality. First, the article examines the impact of the classic power disparity between student and teacher as a dynamic that can trigger recall of the abuse of power inherent in sexual violence. Next the article reframes understandings of trigger warnings to consider how they can be used to support educators in taking seriously the vulnerability of those who have experienced sexual assault. The article also presents perspectives on the role of "teacher self-disclosure" in facilitating conversations that acknowledge sexual assault, followed by a teaching strategy that demonstrates pedagogical sensitivity to trauma. Suggestions on how to support students through and beyond conversations that can trigger traumatic stress conclude the article.